The Effect of Financial Literacy, Income, And Self-Control on The Personal Financial Management of Politeknik Negeri Sriwijaya Students - Aliya Nur Aziza; Devi Septiyani (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The goals of this research is to ascertain how financial literacy, income, and self-control relate to students at Sriwijaya State Polytechnic's individual financial management. A Likert scale is a quantitative research tool that was employed in this research. Data was gathered by mail Google Form surveys to students. The Sriwijaya State Polytechnic class of 2021 students make up the research population. There were thirty responders in the sample. A questionnaire was utilized as the data collecting tool, and the SPSS version 25.0 for Windows computer was used to process the data using the multiple regression analysis technique. The following are the research's findings: Individuals' self-control, income, and financial literacy all have a big impact on how they handle their own finances. Personal financial management is significantly improved by financial literacy. Income significantly and favorably affects how well a person manages their personal finances. The ability to restrain oneself significantly improves management. Personal loans for Sriwijaya State Polytechnic students.